The dwarf & pale leaf mutation reduces chloroplast numbers, resulting in sugar depletion that inhibits leaf growth of maize seedlings - Hamada AbdElgawad; Katrien Sprangers; Sofie Thys; Isabel Pintelon; Bart Cuypers; Mohamed A. El-Tayeb; Clifford Weil; Kris Laukens; Gerrit T.S. Beemster (Current Plant Biology)
Plant growth is ultimately driven by cell division and expansion, but how these processes are regulated to mediate a wide range of genotypic variation in organ size is still poorly understood. To address this, we screened an EMS maize mutant population to identify a new EMS maize dwarf mutant with small, pale-yellow leaves (dpl). The mutation was mapped to a region of 11.58 Mb at the 3’ end of chromosome 7. We identified Zm00001d022394 as a potential causal gene for the dpl phenotype, encoding a pentatricopeptide repeat-containing (PPR) family protein involved in chloroplast gene expression and function, explaining the pale color of dpl. Mature dpl leaves are thinner and shorter due to a reduced number of cells of approximately normal length. The chloroplasts of dpl are reduced in size and number, correlating with a decreased chlorophyll content, however chloroplast ultrastructure was not affected. Consistent with the reduced chlorophyll content photosynthetic rate of dpl were reduced by 50 % and a 30 reduction of Fv/Fm suggests photoinhibition. As a consequence, soluble and insoluble sugar levels are severely reduced throughout the leaf growth zone. At the cell level reduced cell division rates and size of the division zone, explain the reduced leaf elongation rate (LER). The growth of dpl leaves can be restored by supplying growing leaves with sucrose through their cut tips, which also restores sucrose levels in the division zone of maize leaf, demonstrating that limited sugar availability explains the reduced growth phenotype. Inversely, we phenocopied the mutant growth phenotype by inhibiting photosynthetic electron transport in wild type plants with DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea). Our study of dpl provides a functional link between inhibition of photosynthesis, soluble sugar flux to the leaf growth zone, the regulation of cell division and whole leaf growth.